Are Broadband, Computer and Transport Access Inequity Interrelated? - O'Mahony, Margaret (My University, 2025)
Connectivity has become a major issue in socio-economic growth in today’s world. A significant pressure exists on individuals to be connected to society, especially in terms of mobility and technology. This paper examines trends in connectivity in Ireland in the context of accessibility to transport, computer availability and access to broadband. The paper identifies whether certain areas suffer from lack of connectivity and where this inequity exists. Though literature and media exist on certain types of connectivity inequity, few studies have examined whether multiple forms of inequity are interrelated. The study uses Multinomial Logistic (MNL) regression analysis to analyse Irish census data. Inequity was found in transport, broadband and computer access and there appeared to be a degree of interrelatedness between them. How the different levels of access related to deprivation of an area was a key focus of the work. As expected, the proportion of households with broadband and computer access is higher in cities. There are a higher proportion of private transport users in rural areas and a higher mean number of cars per households. Private transport users are more likely to have a long commute time. The proportion of working higher and lower professionals is an indicator of whether broadband and computer access are common in an area. Broadband access is more likely in areas where male unemployment is low, while the affluence of an area affects the likelihood of homes having computer access.
104th Transportation Research Board Annual Conference
Keywords: Inclusive Society; Smart & Sustainable Planet; Transport